2017
DOI: 10.1007/s10801-017-0761-7
|View full text |Cite
|
Sign up to set email alerts
|

Order quasisymmetric functions distinguish rooted trees

Abstract: conjectured that finite trees can be distinguished by their chromatic symmetric functions. In this paper, we prove an analogous statement for posets: Finite rooted trees can be distinguished by their order quasisymmetric functions.has the chromatic polynomial t(t − 1) m−1 then the graph is a tree on m vertices. These results can be found in the introductory article [16].Richard P. Stanley [20] introduced an invariant called the chromatic symmetric function, which is stronger than the chromatic polynomial. For… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 17 publications
1
33
1
Order By: Relevance
“…Hasebe and Tsujie [HT17] have shown the case when all the relations are weak (or all strict), and we generalize their result by establishing Conjecture 1.3 for a class of labeled rooted trees that we call fair trees. We conclude in Section 5 with some directions for further study.…”
Section: Introductionmentioning
confidence: 58%
See 2 more Smart Citations
“…Hasebe and Tsujie [HT17] have shown the case when all the relations are weak (or all strict), and we generalize their result by establishing Conjecture 1.3 for a class of labeled rooted trees that we call fair trees. We conclude in Section 5 with some directions for further study.…”
Section: Introductionmentioning
confidence: 58%
“…• Rooted trees [HT17, Zho20], i.e, posets that are trees with a single minimal element. • More generally, posets that are both bowtie-free and N-free [HT17]. As one would expect, N is the poset consisting of elements a 1 , a 2 , b 1 , b 2 whose cover relations are a 1 < b 1 > a 2 < b 2 , and a poset is N-free if it does not contain N as an induced subposet.…”
Section: Consequences Of the Poset Viewpointmentioning
confidence: 99%
See 1 more Smart Citation
“…In [HT17] (and later in [MW18]) the authors gave a simple description of posets that are both induced N -free and induced bowtie-free which we include here as Definition 10 and Theorem 2.…”
Section: Resultsmentioning
confidence: 99%
“…The order quasisymmetric functions are considered to be analogs of the chromatic symmetric function. A recent study [HT17] by Hasebe and the author showed that the order quasisymmetric functions distinguish rooted trees (with the natural poset structures). The proof is based on algebraic structures of the ring of quasisymmetric functions.…”
Section: Introductionmentioning
confidence: 99%